If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3 + 3(6z + -2) = -7(2z + -2) + 2 Reorder the terms: -3 + 3(-2 + 6z) = -7(2z + -2) + 2 -3 + (-2 * 3 + 6z * 3) = -7(2z + -2) + 2 -3 + (-6 + 18z) = -7(2z + -2) + 2 Combine like terms: -3 + -6 = -9 -9 + 18z = -7(2z + -2) + 2 Reorder the terms: -9 + 18z = -7(-2 + 2z) + 2 -9 + 18z = (-2 * -7 + 2z * -7) + 2 -9 + 18z = (14 + -14z) + 2 Reorder the terms: -9 + 18z = 14 + 2 + -14z Combine like terms: 14 + 2 = 16 -9 + 18z = 16 + -14z Solving -9 + 18z = 16 + -14z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '14z' to each side of the equation. -9 + 18z + 14z = 16 + -14z + 14z Combine like terms: 18z + 14z = 32z -9 + 32z = 16 + -14z + 14z Combine like terms: -14z + 14z = 0 -9 + 32z = 16 + 0 -9 + 32z = 16 Add '9' to each side of the equation. -9 + 9 + 32z = 16 + 9 Combine like terms: -9 + 9 = 0 0 + 32z = 16 + 9 32z = 16 + 9 Combine like terms: 16 + 9 = 25 32z = 25 Divide each side by '32'. z = 0.78125 Simplifying z = 0.78125
| .2x=-1 | | 3x+12=x+14 | | 10p-2(3p-6)=4(3p-6)-8 | | 5x+3=y | | 9(n-3.2)=2(n+0.3) | | X-16=9x | | 26x^2+120x+150=8x^2 | | 8(3x-1)=4(6x+2) | | 0.3-0.7x+2=-8 | | 2=4(x-4)-(x-9) | | 5=-p-12 | | 2(v-1)+4=14 | | 7x+2=x+14 | | 2+3[1+2(4+1)]= | | 6(-y+4)-3(2y-3)=-y+5+5y | | 5p-26=18p | | (c+4)3-6c=2(4-2c) | | 7x+5=-51 | | Hyits=a | | 6m=60 | | 24-2[5-(3*1)]= | | 3=5+3t | | 2x-8=12+3x | | 4x+18-6x+38= | | 0=2t^2-13t+21 | | k+5=4k-10 | | -2x+4=-14 | | (5x^2-7x+7)*(6x+9)=0 | | Y+5=4y-10 | | 7+2s-6=6s+8-3s | | 9x^2-34x-8=0 | | 13t-48=2+14t |